Retrieving history : memory and identity formation in the early church - Laing, Stefana Dan, 1971- (Grand Rapids,MI Baker Academic, 2017)
This volume introduces the early Christian ideas of history and history writing and shows their value for developing Christian communities of the patristic era. It examines the ways early Christians related and transmitted their history: apologetics, martyrdom accounts, sacred biography, and the genre of church history proper. The book shows that exploring the lives and writings of both men and women of the ancient church helps readers understand how Christian identity is rooted in the faithful work of preceding generations. It also offers a corrective to the individualistic and ahistorical tendencies within contemporary Christianity
Map -- Time line -- Invitation to the past -- Ancient historical writing and the rise of historical literary forms -- History as apologetic: harnessing a usable past -- Martyrology: remembering the martyrs' noble example -- Hagiography: martyrdom as discipleship in early Christian biographies -- Ecclesiastical history: the story of the church -- Conclusions and trajectories
Includes bibliographical references (pages 201-209) and index
Keywords: Memory -- Religious aspects -- Christianity; Church history -- Authorship; Church history -- Historiography; Identity (Psychology) -- Religious aspects -- Christianity; Identification (Religion)